18 The Colonial Records of the State of Georgia 117-18 (Allen D. Candler ed., 1910) - (:unkn) unknown (My University, 1755)
Requirement that "any Slave" have a ticket to use a firearm that must be renewed every month, subject to seizure.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES